PHYSICAL QUALITY, IN VITRO DIGESTIBILITY, AND FERMENTATION PRODUCTS OF SILAGE RICE STRAW ADDED VARIOUS TYPES OF LEGUMINOSE - F. K., KIRANA; CAKRA, I G. L. O.; MARIANI, N. P. (Majalah Ilmiah Peternakan, 2022)
This study aims to determine the physical quality, dry matter digestibility, organic matter digestibility, N-NH3, and total VFA of rice straw silage added with various legumes. This research was conducted at Farm Sesetan and at the Laboratory of Animal Nutrition and Forage Laboratory, Faculty of Animal Husbandry Udayana University from No- vember to December 2020. The design used was a completely randomized design (CRD) with five treatments and four replications were P0 (90% rice straw + 5% pollard + 5% mollases), P1 (60% rice straw + 30% Calliandra calothyrsus + 5% pollard + 5% mollases), P2 (60% rice straw + 30% Gliricidia sepium + 5% pollard + 5% mollases), P3 (60% rice straw + 30% Indigofera zollingeriana + 5% pollard + 5% mollases), P4 (60% rice straw + 30% Sesbania grandiflora + 5% pollard + 5% mollases). The results showed that the best values for color, odor, and fungus were obtained in tre- atment P0, P1, and P4. Texture variable got the best value in treatment P0, P1, P2, and P3. The highest of dry matter digestibility and organic matter digestibility values were in the P4. The highest production of total VFA and N-NH3 was produced in treatment P1 and P2. Based on the research results, the addition of various types of legumes added to the rice straw silage can improve the physical quality, dry matter digestibility, organic matter digestibility, N-NH3 and total VFA of the silage.